2017
DOI: 10.1523/jneurosci.0831-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Oscillations Reduce Temporal Long-Range Dependence in Spontaneous Human Brain Activity

Abstract: Ongoing neural dynamics comprise both frequency-specific oscillations and broadband-features, such as long-range dependence (LRD). Despite both being behaviorally relevant, little is known about their potential interactions. In humans, 8-12 Hz α oscillations constitute the strongest deviation from 1/f power-law scaling, the signature of LRD. We postulated that α oscillations, believed to exert active inhibitory gating, downmodulate the temporal width of LRD in slower ongoing brain activity. In two independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 49 publications
10
29
1
Order By: Relevance
“…While this is increasingly recognized in the literature (Becker et al, 2018;Haag et al, 2015;Mahjoory et al, 2019;Tavor et al, 2016), the current study is the first to show this for the theta band oscillations in the context of inhibitory control. Notably, the data analysis of the PLF in Nogo trials revealed no differential effects between the high baseline group and the low baseline group, which was confirmed by Bayesian statistics.…”
Section: Resting Theta Activity Groupingsupporting
confidence: 51%
See 2 more Smart Citations
“…While this is increasingly recognized in the literature (Becker et al, 2018;Haag et al, 2015;Mahjoory et al, 2019;Tavor et al, 2016), the current study is the first to show this for the theta band oscillations in the context of inhibitory control. Notably, the data analysis of the PLF in Nogo trials revealed no differential effects between the high baseline group and the low baseline group, which was confirmed by Bayesian statistics.…”
Section: Resting Theta Activity Groupingsupporting
confidence: 51%
“…In line with overarching theoretical conceptions concerning the function of the medial frontal cortex and theta band activity (Cavanagh & Frank, 2014), the increase in theta band power in Nogo trials has been suggested to reflect an "alarm" or "surprise signal," which is crucial for increasing cognitive control Dippel et al, 2017;Wessel, 2018). On the other hand, it is increasingly recognized that there are similarities between resting dynamics and activity related to cognitive control (Becker, Van de Ville, & Kleinschmidt, 2018;Haag et al, 2015;Mahjoory, Cesnaite, Hohlefeld, Villringer, & Nikulin, 2019;Tavor et al, 2016). Based on these findings, it could be assumed that the individual ability to increase theta activity beyond a certain resting state activity is essential for successful response inhibition performance.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Finally, we wanted to establish whether the suppressed low frequency activity in alHG reflected a reduction in the strength of a narrowband oscillation that is present before stimulus onset, or could be better characterized as a change in the exponent χ ("slope") of the scale-free 1/f χ component of the power spectrum. The latter may reflect properties of neural circuits distinct from those that generate narrowband oscillations (He, 2014;Gao, 2015;Podvalny et al, 2015;Voytek et al, 2015;Becker et al, 2018). The analyses described so far, in which power at each frequency was normalized by its value during a pre-stimulus baseline, cannot differentiate between these two contributions to neural power spectra.…”
Section: Alpha-power Suppression In Anterolateral Heschl's Gyrus Reflmentioning
confidence: 98%
“…Indeed, scale-free temporal dynamics were observed across several modalities, both at rest or during Work supported by ANR-16-CE33-0020 MultiFracs, France task performance, and under various conditions or pathologies [1][2][3][4][5][6][7][8][9][10][11][12]. It has also been documented that scale-free dynamics are functionally associated with neural excitability [3,13] and negatively correlates with power fluctuation in alpha-band (8−12 Hz) [14], hence explaining the modulation of scaling exponents with task engagement or pathologies.…”
Section: Introductionmentioning
confidence: 99%